LEARNING BASIC JAPANESE USING AUGMENTED REALITY (HIRAGANA CHARACTERS AND BASIC COMMUNICATION, hiRAR) - FARAH HAZIQAH, BAHAROM (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Nowadays, people are more interested in learning the Japanese language as a second or third language. Still, at the same time, it requires a lot of practices and a lot of effort to master in the language that we unfamiliar with. The new learners have experienced several challenging aspects in the process of learning the foreign language as a second or third language. Learning process started to get complicated when the interaction between the learning tools and students is scoped down to static text, so it is hard to visualize and failed to focus. This is of the main reasons hirAR mobile application is developed for the students who want to learn the Japanese Language. There are existing systems which help to learn the Japanese language in a fun way, but most of the systems only focus on characters learning but not for learning phrases and communication learning. With the mobile application using Augmented Reality (AR), in education used as learning tools, it provides new digital media that results in teaching and learning enhancement. The main objective of this project is to develop a mobile application platform for Japanese Language studies that will be used by the students who are taking Japanese Language Level 1. By using this application, the mobile app using augmented reality for Japanese learning is proposed to give exposure to the Japanese language learner to explore the Japanese language in an engaging way.